Food sources of vitamin D and their association with 25-hydroxyvitamin D status in Dutch older adults. Issue 173 (October 2017) - Vaes, A.M.M.; Brouwer-Brolsma, E.M.; van der Zwaluw, N.L.; van Wijngaarden, J.P.; Berendsen, A.A.M.; van Schoor, N.; van der Velde, N.; Uitterlinden, A.; Lips, P.; Dhonukshe-Rutten, R.A.M.; de Groot, L.C.P.G.M.
Highlights: Vitamin D intake in older Dutch adults is inadequate (median 4.3 μg/day). Food sources of vitamin D may contribute to counteract modest deficiencies. Butter and margarine are the predominant contributors to vitamin D intake. Without fortified products the habitual diet will not suffice to reach the DRI. Abstract: Various populations are at increased risk of developing a low vitamin D status, in particular older adults. Whereas sun exposure is considered the main source of vitamin D, especially during summer, dietary contributions should not be underestimated. This study aims to identify food sources of vitamin D that associate most strongly with serum vitamin D concentration. Data of 595 Dutch adults, aged ≥65 years, were analysed. Vitamin D intake was assessed with a food frequency questionnaire and 25-hydroxyvitamin D (25(OH)D) was determined in serum. Associations of total vitamin D intake and vitamin D intake from specific food groups with serum 25(OH)D status were examined by P -for trend analyses over tertiles of vitamin D intake, prevalence ratios (PRs), and spline regression. The prevalence of vitamin D deficiency was high, with 36% of the participants having a 25(OH)D status <50 nmol/L. Participants with adequate 25(OH)D concentrations were more likely to be men and more likely to be younger than participants with vitamin D deficiency. Total median vitamin D intake was 4.3 μg/day, of which 4.0 μg/day was provided by foods. Butter and margarine were the leading contributors to total vitamin D intake with 1.8 μg/day, followed by the intake of fish and shellfish with 0.56 μg/day. Participants with higher intakes of butter and margarine were 21% more likely to have a sufficient 25(OH)D status after adjustment for covariates (T1 vs. T3: PR 1.0 vs. 1.21 (95%CI: 1.03–1.42), P -for trend 0.02). None of the other food groups showed a significant association with the probability of having a sufficient 25(OH)D status. This study shows that vitamin D intake was positively associated with total serum 25(OH)D concentration, with butter and margarine being the most important contributors to total vitamin D intake.